Cytotoxic Alkaloids from Leaves of Pilea aff. martinii - Doan Thi Thuy, Ai; Trinh Thi Thanh, Van; Doan Thi Mai, Huong; Le, Huyen Tram; Litaudon, Marc; Nguyen, Van Hung; Chau, Van Minh; Pham, Van Cuong (Planta Medica, 2019)
Two new phenanthroquinolizidine alkaloids (1 and 2) and a new piperidine derivative (3) were isolated from the leaves of Pilea aff. martinii together with 3 known alkaloids: julandine (4), cryptopleurine (5), and 1,3,6,6-tetramethyl-5,6,7,8-tetrahydro-isoquinolin-8-one (6). Their structures were determined by spectral data analyses including mass spectrometry and 2-dimensional nuclear magnetic resonance data. The absolute configurations of 1–3 were established by comparison of their experimental circular dichroism data with the calculated electronic circular dichroism spectra. The isolated compounds were evaluated for their cytotoxicity against 4 cancer cell lines: KB (mouth epidermal carcinoma cells), HepG-2 (human liver hepatocellular carcinoma cells), LU-1 (human lung adenocarcinoma cells), and MCF-7 (human breast cancer cells). The new phenanthroquinolizidine pileamartine D (2) showed strong and selective proliferation inhibition toward KB and HepG-2 cells with IC50 values of 25 and 27 nM, respectively. Pileamartine C (1), julandine (4), and cryptopleurine (5) exhibited cytotoxicity against 4 tested cancer cell lines with IC50 values less than 1 µM.
Keywords: Pilea aff. martinii; Urticaceae; pileamartine; cytotoxic; alkaloid; pileamartine; phenanthroquinolizidine